EMOTIONAL STATE OF JUNIOR SCHOOLCHILDREN WITH DIFFERENT ATTACHMENT STYLES DURING ADAPTATION PERIOD - Razina, N.B. (Modern Psychology, 2020)
This article deals with studies of emotional state of junior schoolchildren with different attachment style to caregiver in the period of adaptation to the first grade. The studies showed that children with various attachment styles show different emotional state: emotional inversion in cognitive sphere is significantly more common among children with insecure attachment style thаn with secure attachment style. The significant correlation was traced between parameter of security in attachment and background emotional performance of junior schoolchildren during adaptation to the first grade. The repeated observation of longitudinal study, the tests showed that emotional state of children with low parameter of attachment style’s security was improved while the emotional state of children with high parameter got worse.
Keywords: emotional sphere, adaptation to school, attachment, attachment style.